PRINCIPLES FOR DEVELOPMENT OF OPTIMIZATION ALGORITHM FOR OPERATIONAL RELIABILITY OF DISTRIBUTIVE SYSTEMS WITH DUE ACCOUNT OF PROBABILITY IMPACT FACTORS - O. E. Gudkova; I. M Savchenko; O. A. Grebenchikov; A. A. Sergeev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Reliability  of  distributive  systems  for  electric supply of consumers is considered as a multi-criteria function. For this reason while developing an algorithm for determination  of  optimum  reliability  level  of distributive networks it is necessary to take into account probability character of changes  in corresponding indices.  A mathematical model and algorithm have been developed for determination of optimum reliability level of electric supply systems with due account of probability changes in reliability indices of component elements.